2020
DOI: 10.18510/hssr.2020.8348
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Social Media Whatsapp Among English Education Students for Solving Thesis Writing Problems

Abstract: Purpose of the study: This study aimed to analyze the use of social media, WhatsApp, among the UIN (Universitas Islam Negeri) Ar-Raniry's English Language Education Program undergraduate students for solving their thesis writing problems, focusing on the effects of the WhatsApp use and to inquire whether WhatsApp communication helps them solve their thesis writing problems. Methodology: The design of this study is descriptive qualitative in nature. The researchers selected 30 English Language Education P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…The WhatsApp application is easy and inexpensive to use, user-friendly, and can write and dispatch messages in real-time (Setiawan & Iasha, 2020). This statement is also following Ahmad et al, which states that using Whatsapp groups a simple, easy-to-use, inexpensive application in the learning process (Ahmad et al, 2020;Sahidillah & Miftahurrisqi, 2019). WhatsApp provides answers to students and helps increase learner guidance feelings they always have their college time.…”
Section: Distance Learning Platformmentioning
confidence: 90%
“…The WhatsApp application is easy and inexpensive to use, user-friendly, and can write and dispatch messages in real-time (Setiawan & Iasha, 2020). This statement is also following Ahmad et al, which states that using Whatsapp groups a simple, easy-to-use, inexpensive application in the learning process (Ahmad et al, 2020;Sahidillah & Miftahurrisqi, 2019). WhatsApp provides answers to students and helps increase learner guidance feelings they always have their college time.…”
Section: Distance Learning Platformmentioning
confidence: 90%
“…The results of several studies indicated that using WhatsApp has a positive effect on macro skills of English language including Reading, Listening, Speaking, and Writing (Abraham & Fanny, 2019;Kartal, 2019) as well as the micro skills _vocabulary and grammar (S. T. S. Kartal, 2019). Regarding Writing, WhatsApp proved to have significant effects (Tarisman & Hanafi, 2020)while (Magogwe & Jaiyeoba, 2019) (S. S. Ahmed, 2019) concluded that using WhatsApp helps developing Academic Writing and (Ahmad et al, 2020;Kaid Mohammed Ali & Rashad Ali Bin-Hady, 2019;Magogwe & Jaiyeoba, 2019) highlighted the development of thesis writing after using WhatsApp, as well as (Tarisman & Hanafi, 2020) who mentioned the development of critical and descriptive writing through WhatsApp. In addition to writing, WhatsApp also plays a significant role in improving reading (S. S. Kaid Mohammed Ali & Rashad Ali Bin-Hady, 2019) and, indeed, critical reading skills (Tarisman & Hanafi, 2020).…”
Section: Skillsmentioning
confidence: 99%
“…As mentioned above, (Baguma et al, 2019) asserted that WAEL can contribute to HOTS (such as critical thinking and problem solving). (Ahmad et al, 2020) narrowed down the problem-solving skill into academic writing in an Indonesian context and found that WhatsApp could help students share, discuss, and solve their problems regarding their thesis writing. Similarly, (Chng, 2020) investigated the educational use of WhatsApp among digital immigrants and claimed that peer interaction in the WhatsApp group chats allowed students to talk more about how to solve problems faced in the assignments and discuss possible exam topics.…”
Section: Learning Skillsmentioning
confidence: 99%
“…Using social media, people can communicate about life issues such as education, politics, family, faith, etc. (Ahmad et al, 2020;Zainal et al, 2022). Smartphones are a tool for accessing social media.…”
Section: Introductionmentioning
confidence: 99%